Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Dan Komitmen Organisasi Terhadap Kinerja Pegawai Melalui Organizational Citizenship Behavior Sebagai Variabel Intervening Pada Kementerian Pemuda Dan Olahraga (Deputi I) - I Wayan Darmawan; Suryono Efendi (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze between Leadership Style, Organizational Culture, Organizational Commitment to Employee Performance of the Ministry of Youth and Sports through organizational Citizen Behavior using a quantitative approach method, survey method using path analysis. Data collection in this study used a questionnaire questionnaire, with data analysis techniques using SmartPLS SEM (Partial least Square - Structural Equation Modeling) software. The results show that Leadership Style, Organizational Culture, Organizational Commitment directly have a positive and significant effect on employee performance. Leadership Style, Organizational Culture, Organizational Commitment directly have a positive and significant effect on Organizational Citizen Behavior (OCB) as an intervening variable. Furthermore, Leadership Style, Organizational Culture, Organizational Commitment directly have a positive and significant effect on Organizational Performance through Organizational Citizen Behavior (OCB).